A Synergy of Halal Tourism Regulations and Tourism Rights Protection in Aceh: Pentahelix Model - Rahayu, Sri Walny; Abbas, Syahrizal (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2024)
Aceh has tourism regulations and guarantees of halal food products. This sector can potentially grow the regional economy and develop Aceh. Utilizing the tourism sector should allow the Aceh region to develop regional potential and increase regional income. However, in practice, the regulations do not optimally accommodate strategic issues that can support regional development from tourism sources. Still, the regulations have guaranteed protection for all consumers and tourists visiting Aceh as a halal destination. This study examines tourism regulatory policies and guarantees of halal food products using the pentahelix model. This study uses normative juridical methods and then analyzed descriptively and comprehensively. The data comes from literature studies, namely studies of theoretical documents in the form of articles, legal regulations, books and various studies related to the discussion. The results of the study showed that tourism regulatory policies and guarantees of halal food products in Aceh have not yet synergized with the pentahelix model in determining technical policies regarding tourism management and halal food product guarantee. This may lead to neglected protection of basic consumer rights, low quality and diversity of tourist attractions, and limited availability and quality of accessibility services and tourism facilities to reach potential markets. On the other hand, Aceh is a region that applies Islamic law and has strong religious characteristics, so the role of ulama can be used in making halal food policies to support the development of Islamic tourism.